If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -2 + 7x = -9 Reorder the terms: -2 + -8x + 7x = -9 Combine like terms: -8x + 7x = -1x -2 + -1x = -9 Solving -2 + -1x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = -9 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -9 + 2 -1x = -9 + 2 Combine like terms: -9 + 2 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 13=2x+15 | | -2(2x+4)=-16 | | 2x-21-x+10=-1 | | 3(x+8)=45 | | 7(1+2x)=147 | | -6=11x-5x | | 5x+2(6)=3x(11) | | 15=5-2x | | 6(2x+7)=126 | | -4(-2+5x)=28 | | X^2+4xy+5x=0 | | (-3)/(-10)*0*(-2)= | | -5(7+7x)=-105 | | 3x+12-4x=20 | | 8x+7=x-1 | | -4(-7+6x)=-236 | | x^2+-20x+39=0 | | d^2+8c+12=0 | | -4+4x=2x+14 | | 6x+6=-2+7x | | 5x^2-22=0 | | 2x-7=7x-32 | | 15.4c-13.7=14x-17.2 | | -4+7X=-2x-94 | | 6x+6=-4x+6 | | 4(3+2x)-7= | | (-21)/3-5*(-5)= | | 4y+16x=20 | | .75(x+2)-(2/3)(x-3)=2 | | 4x-115=95-11x | | 3y=9x-3 | | 6x+10=x+60 |